FLUKTUASI HARGA SAHAM DAN VOLUME TRANSAKSI SAHAM SEBELUM DAN SESUDAH PENGUMUMAN COVID-19 PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BEI - Angrawit Kusumawardani (Jurnal Apresiasi Ekonomi, 2022)
This research aims to determine fluctuations in stock prices and stock trading volumes in pharmaceutical companies listed on the IDX. The population used is eight pharmaceutical companies listed on the Indonesia Stock Exchange. The data was processed using paired sample-t-test. From the results of the preparation of this information, it is known that there is a very striking difference in stock prices before and after the announcement of the coronavirus case in Indonesia. This is evidenced by a significance value of less than 0.05, where the share value has decreased in contrast to before the announcement. Meanwhile, the transaction volume shows a critical difference with a significance value of less than 0.05, where the transaction volume after the notification has increased.